PARLIAMENTARY THRESHOLD IN PERSPECTIVE OF GENERAL STATEMENT AND MODERN LAW - Sholahuddin Al-Fatih (Jurnal Hukum Replik, 2020)
This research tries to discuss the characteristics of modern law contained in Law No. 7 of 2017 on Elections. Through conceptual and legal approaches, this research tries to examine the concept of the relationship between the character of modern law and one of the legal products in Indonesia, namely Law No. 7 of 2017 on Elections. This research made Marc Galanter's thinking on the concept of modern law a benchmark and an analytical knife. The results of this study suggest that theoretically the product of regulation regarding election law in Law No. 7 of 2017 on Elections can be referred to as modern law. This research is expected to help academics and practitioners of election law to be able to dig deeper into the characteristics of modern law, not only based on the ideas of Marc Galanter but also by other thinkers or experts.Keywords: Character; Law, Modern; Election